GAMBARAN KEPUASAN PASIEN TERHADAP PELAYANAN GIGI DAN MULUT DI POLI GIGI - Arum, Maulina (Poltekkes Kemenkes Bandung, 2025)
Satisfaction is a response to fulfilling consumer needs. This is related to the assessment that the product or service itself provides a level of satisfaction where this level of fulfillment can be more or less. The purpose of this study was to obtain an overview of patient satisfaction with dental and oral services at the Dental Clinic of the Kepuh Health Center, Cirebon Regency. The research method uses descriptive research, namely to determine patient satisfaction at the Kepuh Health Center Dental Clinic. The research was conducted in April and May 2015 at the Dental Clinic of the Kepuh Health Center, Cirebon Regency. The population in this study were patients who visited the Dental Clinic at the Kepuh Health Center in Cirebon Regency who had received dental and oral health services. The sampling technique used was accidential sampling, so that a sample of 67 respondents was obtained. The results of measurements of time satisfaction and service rates show that patients are satisfied. The measurement results of the service mechanism, the patient is satisfied. The results of measurements of the services of health workers in providing health services, the average patient is satisfied. As well as the results of measurements of facilities and infrastructure, patients are satisfied.